2022
DOI: 10.1007/s00330-021-08435-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of semiquantitative chest CT scoring systems to estimate severity in coronavirus disease 2019 (COVID-19) pneumonia

Abstract: Objectives To compare the clinical usefulness among three different semiquantitative computed tomography (CT) severity scoring systems for coronavirus disease 2019 (COVID-19) pneumonia. Methods Two radiologists independently reviewed chest CT images in 108 patients to rate three CT scoring systems (total CT score [TSS], chest CT score [CCTS], and CT severity score [CTSS]). We made a minor modification to CTSS. Quantitative dense area ratio (QDAR: the ratio of lung invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
13
1
2
Order By: Relevance
“…According to a previous study conducted in the early phase of the pandemic, the typical appearance of COVID-19 pneumonia on chest CT was mainly reported as ground-glass opacities (GGOs) [ 3 ], and several studies have shown that the extent and density of pulmonary inflammatory lesions, predominantly GGOs, are associated with poor prognosis of COVID-19 [ 4 – 9 ]. Semi-quantitative scoring systems based on measurement of the volume of lung segment affected have been established as a reliable approach to predict the clinical severity of COVID-19 [ 6 , 10 12 ]. The appearance of GGOs, a key radiological manifestation of COVID-19, reflects pulmonary edema and hyaline membrane formation induced by inflammation from SARS-CoV-2 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study conducted in the early phase of the pandemic, the typical appearance of COVID-19 pneumonia on chest CT was mainly reported as ground-glass opacities (GGOs) [ 3 ], and several studies have shown that the extent and density of pulmonary inflammatory lesions, predominantly GGOs, are associated with poor prognosis of COVID-19 [ 4 – 9 ]. Semi-quantitative scoring systems based on measurement of the volume of lung segment affected have been established as a reliable approach to predict the clinical severity of COVID-19 [ 6 , 10 12 ]. The appearance of GGOs, a key radiological manifestation of COVID-19, reflects pulmonary edema and hyaline membrane formation induced by inflammation from SARS-CoV-2 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we did not obtain detailed clinical data about the severity of COVID-19 pneumonia in our study population. Nonetheless, the CCS is an established imaging biomarker for severity of COVID-19 pneumonia, and has been suggested a surrogate parameter for the clinical course of the disease by several authors ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 ) ( 23 ). We used the CCTS as it has been demonstrated to show the best performance among the three semiquantitative CT scoring systems, namely, CCTS ( 23 ), total CT score ( 24 ), and CT severity score ( 25 , 26 ). The radiologist reviewed the chest CTs with the lung window setting and evaluated the extent of disease involvement using a five-point scale (0: 0%, 1: 0-4%, 2: 5-25%, 3: 26-49%, 4: 50-75%, and 5: 76-100%) for five lung lobes.…”
Section: Methodsmentioning
confidence: 99%